Notions for revising epistemic research principles: A decolonized outlook (2010)
With ever more force, the last few years have given shape to a rising group of thinkers who started questioning the current colonialism of knowledge, power and being, andwhose thoughts and contributions have also begun identifying solutions to the hegemonic epistemic dependence of countries ‘condemned’ by the modern world-system (Wallerstein, 1999). Accordingly, the article encourages reviewing the epistemological foundations that govern research in Colombian university faculties, offering ideas or principles for starting an academicdialogue with teachers, researchers and students.